2019
DOI: 10.2147/opth.s163089
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inverted internal limiting membrane (ILM) flap technique for macular hole closure: patient selection and special considerations</p>

Abstract: This paper reviews the current status of the newer inverted internal limiting membrane flap technique for macular hole surgery. It gives an overview of the importance of patient selection and special considerations along with variations in technique. It discusses the pathophysiology and how the technique has been an important addition in the armamentarium of vitreoretinal surgeons to attain better anatomical as well as functional results in challenging situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
11
0
1
Order By: Relevance
“…This has been seen with the introduction of the inverted ILM flap technique, which has demonstrated higher success rates for closure of large MH than techniques that use ILM peeling alone. 8 The precise mechanism of the inverted ILM flap technique is not yet clearly understood. It is possible that the flap acts as a scaffold for glial cell proliferation leading to closure of the hole.…”
Section: Discussionmentioning
confidence: 99%
“…This has been seen with the introduction of the inverted ILM flap technique, which has demonstrated higher success rates for closure of large MH than techniques that use ILM peeling alone. 8 The precise mechanism of the inverted ILM flap technique is not yet clearly understood. It is possible that the flap acts as a scaffold for glial cell proliferation leading to closure of the hole.…”
Section: Discussionmentioning
confidence: 99%
“…As evident by various studies, preoperative hole size was the only predictor of postoperative VA, which is inversely proportional to VA gain. [ 20 21 22 23 ] A retrospective study on 50 eyes showed a decrease in VA by 10% for every 26-mm increase in the BHD. [ 14 ] However, in our study, despite including extremes of BD, ranging from 464 to 9778 microns, no such trend was seen and the odds of VA change associated with BD were negligible.…”
Section: Discussionmentioning
confidence: 99%
“…2 ] superior to conventional ILM peeling. [ 24 ] Michalowski et al . [ 12 ] found anatomical closure rate was higher in inverted ILM flap technique (98%) compared to conventional ILM peeling (88%).…”
Section: Discussionmentioning
confidence: 99%